2016
DOI: 10.1590/0034-7167.2016690321
|View full text |Cite
|
Sign up to set email alerts
|

Ausência de expectativa de suporte para o cuidado aos idosos da comunidade

Abstract: it is necessary to reflect upon the formal support system currently available for older people in Brazil, considering that those who most frequently presented lack of anticipated support for care are an increasing population. The study also highlights the importance of using subjective methods for the evaluation of the adequacy of older adults' support network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
1
3
0
8
Order By: Relevance
“…The socio-demographic profile of the elderly presented characteristics similar to other studies, i.e. a predominance of women 4,26 , who were younger than 75 1,4,18,[27][28][29][30] , cohabited with others 4,26,28,30 , had up to two diseases 4, 26-28 and were independent for BADL (85.92%). It is common, as the SABE study showed, that the development of dependence is greater for women (33.2%), the elderly (59.46%) and widowers (37.3%) 4.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The socio-demographic profile of the elderly presented characteristics similar to other studies, i.e. a predominance of women 4,26 , who were younger than 75 1,4,18,[27][28][29][30] , cohabited with others 4,26,28,30 , had up to two diseases 4, 26-28 and were independent for BADL (85.92%). It is common, as the SABE study showed, that the development of dependence is greater for women (33.2%), the elderly (59.46%) and widowers (37.3%) 4.…”
Section: Discussionsupporting
confidence: 71%
“…Almost 1/3 of those who lived alone complained of suffering from an illness in the two weeks prior to the interview, the majority self-reported difficulties with IADL; falls (previous 12 months) and worse eating habits are also related to the elderly who live alone 29 . Most of the elderly lived with someone else 1,27,28,30,31 and, among their families, across generations, establish a comfortable reciprocity in giving and receiving help, especially material and emotional support 32 .…”
Section: Analysis Of Information From the Nationalmentioning
confidence: 99%
“…In general, informal care is expected to be carried out by family members, with this characteristic influenced by cultural and religious norms 34 . In the context of vulnerability, low incomes limit support for care or ways of paying for this service.…”
Section: Discussionmentioning
confidence: 99%
“…Se cercado de cuidados, o processo de envelhecimento pode ser vivenciado como um momento de prazer (Dawalibi, Anacleto, Witter, Goulart, & Aquino, 2013). A oferta de apoio social ao público idoso é considerada um aspecto de proteção em nível de bem-estar psicológico e físico, sendo atribuído a este fator protetivo a redução na taxa de mortalidade desse grupo (Oliveira, Neri & D'Elboux, 2016). Para que venham a ser geradas formas interventivas, em busca de melhor qualidade de vida desses idosos, se faz necessária uma mobilização no campo da educação, da saúde, de serviços sociais e da família (Resende & Rabelo, 2004;Silva, Souza & Crepaldi-Alves, 2015), a fim de que tais dados possam facilitar o desenvolvimento e implementação de políticas públicas (Carvalho, Luckow, Peres, Garcias, & Siqueira, 2012) dentro da visão da psicologia positiva.…”
Section: Discussionunclassified